Jawahar Linseed Sagar-66 (JLS-66): Development and dissemination of newly developed linseed variety for nutritional security of India: SAGAR-66 (JLS-66): DEVELOPMENT OF NEW LINSEED VARIETY FOR NUTRITIONAL SECURITY OF INDIA - DEVENDRA K PAYASI; M P DUBEY (Journal of Oilseeds Research, 2020)
A linseed cultivar 'Jawahar Linseed Sagar 66 (JLS-66)' has been released in Madhya Pradesh for cultivation under rainfed cropping situations by the State Sub- Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops, Government of Madhya Pradesh, Bhopal. It matures in 114 days, yields 1200 kg seed/hectare and contains 42.85 per cent drying oil. In All India coordinated trials, JLS-66 gave 11.11, 12.99, 10.80 and 20.97% higher seed and 21.51, 22.67, 16.03 and 37.80% higher oil yields over the prevailing varieties viz., JLS-67, NL-97, JLS-9 and T-397, respectively of the zone III comprising Bundelkhand part of UP, Rajasthan and Madhya Pradesh. It has resistance to major diseases and the most obnoxious pest, bud fly and is tolerant to moisture and high temperature stresses. The variety has recorded high alpha linolenic acid (55.96 %) which is known as Omega-3 and directly influences the quality of oil. Hence, on one hand the cultivators will be benefited with this variety containing high level of oil and quality, and on the other hand industrialists will also be benefitted by getting good nutritive raw material for their industries especially Omega-3 which has medicinal value